Feeling good, but missing the mark. What happened to the assessment in peer assessment? - Sandvoll, Ragnhild (Journal of University Teaching and Learning Practice, 2014)
This qualitative study explores aspects of formative peer assessment through looking at teachers’ and students’ perceptions and practices. The study takes place in a first semester course, where mastering peer assessment was a learning outcome and where formative peer assessment was designed into the course plan as a learning activity. Empirical material is derived from observing two seminar groups and from interviewing teachers and students. Findings indicated that whilst all interviewees expressed positive attitudes towards peer assessment, no one seemed to put much effort into doing it. Using Argyris’ theories of action as a theoretical framework, the study explores the relationship between realities of practice and espoused theories. Discussion focuses on the apparent paradox of positive expressed views and minimal effort. Additionally, the role of the teachers in managing peer assessment will be discussed, linked to the development of their teaching.